2009
DOI: 10.1096/fj.09-139147
|View full text |Cite
|
Sign up to set email alerts
|

Gene delivery to mitotic and postmitotic photoreceptors Via compacted DNA nanoparticles results in improved phenotype in a mouse model of retinitis pigmentosa

Abstract: The purpose of the present study was to test the therapeutic efficiency and safety of compacted-DNA nanoparticle-mediated gene delivery into the subretinal space of a juvenile mouse model of retinitis pigmentosa. Nanoparticles containing the mouse opsin promoter and wild-type mouse Rds gene were injected subretinally into mice carrying a haploinsufficiency mutation in the retinal degeneration slow (rds(+ or -)) gene at postnatal day (P)5 and 22. Control mice were either injected with saline, injected with unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 42 publications
1
117
1
1
Order By: Relevance
“…We constructed CK30PEG NP-carrying (4.3 mg DNA/ml) vectors (13-14 kbp) with the human ABCA4 cDNA and the photoreceptor-specific human interphotoreceptor retinoid-binding protein (IRBP-ABCA4) promoter or the mouse opsin (MOP-ABCA4) promoter (1,2) and confirmed that the NPs carried intact plasmid (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI64833DS1). NPs carrying nonfunctional mutant ABCA4 (K969M, ref.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…We constructed CK30PEG NP-carrying (4.3 mg DNA/ml) vectors (13-14 kbp) with the human ABCA4 cDNA and the photoreceptor-specific human interphotoreceptor retinoid-binding protein (IRBP-ABCA4) promoter or the mouse opsin (MOP-ABCA4) promoter (1,2) and confirmed that the NPs carried intact plasmid (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI64833DS1). NPs carrying nonfunctional mutant ABCA4 (K969M, ref.…”
Section: Resultsmentioning
confidence: 72%
“…Compacted DNA nanoparticles (NPs) (8-10 nm in diameter) formulated with polyethylene glycol-substituted polylysine (CK30PEG) are highly efficient in transfecting postmitotic cells (1)(2)(3)(4)(5), are biodegradable (3,4), and exhibit minimal toxicity, even after repeated dosing, to the eye, lung, and brain (1,2,(5)(6)(7). In contrast with many other nonviral approaches, these NPs drive long-term gene expression (1,2) after subretinal delivery to the mouse eye, making them an excellent choice for chronic retinal degenerations such as Stargardt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantages of such physico-chemical approaches include the fact that there are no size limitations with respect to the transgene cassette and that the approach does not deliver additional antigens besides the DNA/DNA-binding reagents themselves. Potential disadvantages include concern about longevity of expression and efficiency of nuclear entry, although a recent report using compacted DNA nanoparticles showed evidence of marked physiologic rescue for at least 30 days after delivery (26).…”
Section: Gene Augmentation Therapy Considerationsmentioning
confidence: 99%
“…In addition, in contrast with other nonviral approaches, CK30-NPs drive long-term gene expression after subretinal delivery to the mouse eye . Given the success of CK30-NPs to mediate phenotypic rescue in rodent models of retinitis pigmentosa (Cai et al 2009(Cai et al , 2010 and their favorable safety and efficacy profile in a human clinical trial for cystic fibrosis (Konstan et al 2004). Han et al (2012) have recently tested CK30-NPs for ABCA4 delivery in the Abca4…”
Section: Nonviral Gene Delivery In Abca4-associated Diseasesmentioning
confidence: 99%